Laser ablation behavior subjected to subsonic airflow at different spatial positions - Xiaoying LIU; Chenghua WEI; Shuyu HUANG; Fenggui LU (Hanjie xuebao)
In order to study the interactions between laser energy, surface airflow, spatial position and metal materials in the process of laser ablation, a fluid-structure-coupled laser ablation model considering the combined action of subsonic tangential flow and spatial position of workpiece to induce melt removal is proposed, and by comparison with high-speed images, the rationality of the model is verified. The interaction process between surface airflow and large-scale molten pool and melt peeling off behavior are studied at different spatial positions. It is found that induced by the combined action of airflow and spatial position, on one hand, the melt is pushed out of the molten pool to form a tilted liquid column and accelerated to 1.6 m/s or even higher, providing high momentum for the melt to peel away from the molten pool, on the other hand, the liquid column is elongated to be slender to be only 0.45 mm thick, which easily overcome the melt surface tension, causing the melt to peel off and form spatter. Adjusting the metal spatial position and reducing α from 90° to 30°, the component of gravity along the metal surface irradiated by laser is accordingly reduced. The melt flow velocity in the liquid column slows down from 1.6 m/s to 1.4 m/s. The size of ablation crater formed by melt peeling off decreases gradually, and both the peeling-off degree of molten pool and the metal mass loss are reduced significantly.